INTERDISCIPLINARY RESEARCH AS PRIORITY VECTOR OF PROFESSIONAL PEDAGOGY - N. Diachok (Borys Grinchenko Kyiv Metropolitan University, 2017)
The article deals with the relationship of interdisciplinary research in professional pedagogy. It is stressed on the basic components of professional pedagogy as general pedagogy, general and educational psychology, engineering psychology, work psychology, acmeology. The article gives the analysis of connection between interdisciplinary researches in professional pedagogy, which is reflected in integration of the interdisciplinary educational complex in the conditions of European integration. The purpose of the article is to give the reader some information on interdisciplinary relationships in professional pedagogy which appear as a way of competitive graduates' development. Today it is extremely important for a job to obtain full experience in chosen profession. Nowadays it is defined quite clearly the way of preparation and evaluation of the achievements of graduates. It is the way of comparison with using parameters passport competencies of professional standard. Much attention is given to the opinion of Bochan who says that nowadays educational pedagogical activity is the introduction of new learning technologies, integrated courses, and development of new interdisciplinary connections. It is spoken in detail about establishing interdisciplinary relations in professional disciplines which is an important part of the concept of interdisciplinary integration, which involves combining knowledge, beliefs and practical action at all the stages of training, the synthesis of all forms of employment in relation to each particular purpose of education in universities. In conclusion, the author considers that the manifestation of interdisciplinary relations in professional pedagogy is the integration process which is the important element of combining general and vocational education in the integrated system of training, as a result of this way is bridging the gap between theory and practice in contemporary higher education.